Characteristics and suitability of some arid soils in Southeastern Iran for wheat cultivation - Moghimi, Abolhassan; Jol, Hamdan (Academic Journals, 2014)
A study was conducted to characterize the calcareous soils of the Askara plain in Southeastern Iran and evaluate their potential for wheat production. Sixteen soil profiles within the colluvial fan in different physiographic units were studied. Four phases of soils were identified namely the Ashkara, Dareabad, Khalandi, and Sheikhabad soils. All soils were classified as Entisols, namely Aridic Ustortents and Aridic Ustifluvents. The Ashkara soils were marginally suitable while the Dareabad and Khalandi soils were moderatelly suitable for wheat growing. The Sheikhabad soil units, however, were evaluated as S1, S2, S3 and N1 classes. The results suggested that most important limiting are high CaCO3, pH, texture and salinity as the major constraints to wheat productivity for soils of the Ashkara plain. There are about 60% of the plain that are suitable for wheat growing and only 1.15% that is not suitable due to poor moisture availability. The rest 38.85% of the plains are marginal soils.